"Bercadar Itu Pengakuan"; Reproduksi Makna Cadar di Kalangan Pengguna - Vivi Sartika; M. Yusuf (Indonesian Journal of Religion and Society, 2020)
This study aims to explain the production and reproduction of the meaning of the niqab among the female student who wear niqab at UIN Imam Bonjol Padang. This study used a qualitative research method (field research), with data collection using in-depth interviews with several female students that wearing the niqab at UIN Imam Bonjol Padang. This study uses Antony Giddens' structuring theoretical approach and focuses on how the female student who wearing the niqab produce and reproduce the meaning of the niqab in education. This study found that the actions of wearing the niqab take have created resources for female who wearing niqab in education. These resources can be seen from the reproduction of the meaning of the niqab as a form of applying religious doctrines (personal protection) and the niqab as a form of power (praying for individuals to wear the niqab). This study draws the conclusion that the resource is born on the basis of the practice of the women who wear niqab, but on the other hand, the practice is born in a structure that is restrictive and liberating.